2011
DOI: 10.1007/s00408-011-9318-z
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Volume Dependence of Rat Airway Resistance During Constant Flow Inflation and Deflation

Abstract: The observed flow and volume dependence of respiratory system resistance may be predicted by an equation derived from a model of the respiratory system that consists of two distinct compartments. The equation agrees well with the experimental data and indicates that the loading time is the critical parameter on which stress relaxation depends, during both lung inflation and deflation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…The global resistances and compliances identified in this study agreed well with previously published data, 21,42,49 despite the limited experimental data available in this current study (Table 4). While the previous studies reported higher compliance values, the relative increase in compliance between emphysematous and healthy rats was similar.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The global resistances and compliances identified in this study agreed well with previously published data, 21,42,49 despite the limited experimental data available in this current study (Table 4). While the previous studies reported higher compliance values, the relative increase in compliance between emphysematous and healthy rats was similar.…”
Section: Discussionsupporting
confidence: 92%
“…Resistance during exhalation was set to 1.5 times the resistance during inhalation following previous work. 42 Once the R and C parameters were found for each rat, the volume and flow rate throughout the full breathing cycle were numerically calculated by solving equation 2. The average and standard deviation in each rat category were calculated for the maximum pressure, resistance, compliance, maximum flow rates during inhalation and exhalation.…”
Section: Methodsmentioning
confidence: 99%
“…The mean heart rate values reported here are similar to those expected in normal rats under general anesthesia [28]. As expected, body temperature increments caused a related increase in heart rate [9], which could have increased pulmonary blood flow, which is known to affect lung mechanics [29].…”
Section: Discussionsupporting
confidence: 87%
“…their relaxation times are the same. Following our previous work [22], the 0D resistance during expiration was set to 1.5 times the 0D resistance during inhalation ( R i , j ex = 1.5 R i , j ) [26]. …”
Section: Methodsmentioning
confidence: 99%